Manufacturing sector in Pakistan: A Comprehensive Review for the Future Growth and Development - Rahman, Saif ur; Abu Bakar, Nor'Aznin (Society for Education and Economic Development (SEED), 2019)
The key objective of the present study is to provide a comprehensive review of the manufacturing sector and its growth from the context of Pakistan. For this purpose, decent review of existing literature with the industrial output is provided while taking some other regions as well. Review of the empirical findings of existing literature and industrial output explains that there is a great need of sect-oral growth in Pakistan in present time. The country is facing various issues like higher inflation, low employment opportunities, declining foreign investment and very little focus on economic growth. For the long run financial stability in the economy, significant policy development and implication is a need of time through which more economic development and growth can be achieved. However, a key limitation of the study is not contributing in an empirical context regarding the economic growth,manufacturing sector and its present contribution while taking the economic indicators like GDP, export and import etc. Originality/value of the study can be viewed through its contribution in existing literature while considering the manufacturing sector which is not very well addressed in the earlier literature.